Carotid Body Detection on CT Angiography - Nguyen, R.P. (AJNR Am J Neuroradiol, 2011)
BACKGROUND AND PURPOSE: Advances in multidetector CT provide exquisite detail with improved delineation of the normal anatomic structures in the head and neck. The carotid body is 1 structure that is now routinely depicted with this new imaging technique. An understanding of the size range of the normal carotid body will allow the radiologist to distinguish patients with prominent normal carotid bodies from those who have a small carotid body paraganglioma. MATERIALS AND METHODS: We performed a retrospective analysis of 180 CTAs to assess the imaging appearance of the normal carotid body in its expected anatomic location. RESULTS: The carotid body was detected in >80% of carotid bifurcations. The normal size range measured from 1.1 to 3.9 mm ± 2 SDs, which is consistent with the reported values from anatomic dissections. CONCLUSIONS: An ovoid avidly enhancing structure at the inferomedial aspect of the carotid bifurcation within the above range should be considered a normal carotid body. When the carotid body measures >6 mm, a small carotid body paraganglioma should be suspected and further evaluated.